Exploiting the Optical Limits of Thin‐Film Solar Cells: A Review on Light Management Strategies in Cu(In, Ga)Se2. Issue 6 (22nd January 2022) - Oliveira, António J. N.; Teixeira, Jennifer P.; Ramos, Duarte; Fernandes, Paulo A.; Salomé, Pedro M. P.
Abstract : Light management strategies are of utmost importance to allow Cu(In, Ga)Se2 (CIGS) technology market expansion, as it would enable a conversion efficiency boost as well as thinner absorber layers, increasing sustainability and reducing production costs. However, fabrication and architecture constraints hamper the direct transfer of light management architectures from other photovoltaic technologies. The demand for light management in thin and ultrathin CIGS cells is analyzed by a critical description of the optical loss mechanisms in these devices. Three main pathways to tackle the optical losses are identified: front light management architectures that assist for an omnidirectional low reflection; rear architectures that enable an enhanced optical path length; and unconventional spectral conversion strategies for full spectral harvesting. An outlook over the challenges and developments of light management architectures is performed, establishing a research roadmap for future works in light management for CIGS technology. Following the extensive review, it is expected that combining antireflection, light trapping, and conversion mechanisms, a 27% CIGS solar cell can be achieved. Abstract : Advanced light management strategies are still not fully exploited in state‐of‐the‐art Cu(In, Ga)Se2 (CIGS) devices. Leaps and bounds still must be made to reach or even surpass its optical limits. Hence, a critical overview of the developed light management strategies in CIGS solar cells is provided, establishing a research roadmap for future works in light management for CIGS solar cells.